Family support and quality of life among urban elderly people: A cross-sectional study in Dhaka, Bangladesh (Al-Sihah : The Public Health Science Journal, 2025)
In Bangladesh, the elderly population is expected to rise from 8.2% in 2011 to 11.6% in 2026, which is associated with an increasing burden of chronic diseases that negatively affect the quality of life of the elderly. Previous research on the quality of life (QOL) of the elderly in Bangladesh has given limited focus on the elderly in urban settings within a healthcare setting and the impact of family support. This study aimed to examine the relationship between family support and quality of life among urban elderly people in Bangladesh. A hospital-based cross-sectional study was done among elderly attendants of Dhaka Medical College Hospital with convenience sampling. Data collection was done using a structured questionnaire consisting of socio-demographic data, Family Support Scale (FSS) and WHOQOL-BREF Scale. Statistical analyses, such as independent t-tests, Pearson’s correlation and ANOVA, were performed. About half of the respondents perceived poor family support, and 46.7% had poor overall QOL. Family support was found to have a significant positive correlation with QOL (r = 0.754, p < 0.01). Male gender (p = 0.024), higher education (p < 0.01), absence of chronic disease (p < 0.01), non-smoker (p < 0.01) and joint family living (p < 0.01) were found to be significantly associated with better QOL. These results emphasize the need to strengthen family support and chronic disease management in the city, and suggest that reinforcement of traditional family networks as well as improving access to healthcare may improve the quality of life in the elderly rural populations.